Comparative Transcriptional Profiling of Motor Neuron Disorder-Associated Genes in Various Human Cell Culture Models - Hauser, Stefan; Schuster, Stefanie; Heuten, Elena; Höflinger, Philip; Admard, Jakob; Schelling, Yvonne; Velic, Ana; Macek, Boris; Ossowski, Stephan; Schöls, Ludger (Frontiers in Cell and Developmental Biology, 2020)
Disease modelling requires appropriate cellular models that best mimic the underlying pathophysiology. Human origin and an adequate expression of the disease protein are pre-requisites that support information from a model to be meaningful. In this study we investigated expression profiles of (i) PBMCs and (ii) fibroblasts as patient derived cells as well as (iii) lymphoblasts and (iv) induced pluripotent stem cells (iPSC) as immortalized sources and (v) iPSC-derived cortical neurons to assess their aptitude to model motor neuron diseases (MNDs) including hereditary spastic paraplegia (HSP), amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA). We generated all five cell lines from two healthy donors and performed RNA sequencing to display expression patterns in MND-related genes. For the ten most common HSP genotypes we validated gene expression by qPCR. To verify the results on protein level, proteome analysis of fibroblasts, iPSCs and cortical neurons was performed. Depending on the specific MND gene we found largely different expression patterns. Out of 168 MND-related genes, 50 had their highest expression in iPSC-derived cortical neurons, 41 were most strongly expressed in fibroblasts, 26 in lymphoblasts, 22 in iPSCs, and 14 in PBMCs. Pathophysiologically related MNDs like HSPs associated with axonal transport deficits shared highest expression in cortical neurons. 15 MND-related genes were not detectable in any of the analyzed cell types. This may reflect the critical dependency of motor neurons on support of other cell types like oligodendrocytes which express myelin proteins like L1CAM (SPG1), PLP1 (SPG2) and MAG (SPG75) which are lacking in neurons but cause MNDs if mutated. This study provides comprehensive information on expression of genes associated with a large spectrum of MNDs. Expression profiles can be used to inform on appropriate cell models for genotype specific motor neuron research.